Prisoners’ Right to Vote in The Gambia: A Need for Legal Reform? - Mendy, Ousu; Sarr, Ebrima (West Science Law and Human Rights, 2025)
Prisoners’ right to vote in The Gambia continues to be a less challenged issue both in practice and in theory in state politics since it regained independence. This research assesses state on prisoners’ right to vote and how this defines the state’s governance system towards prisoners from international human rights perspective. An analysis of this issue in the state since it regained political independence reveals how casual academics and policymakers approach it. This piece, therefore, examines human rights perspective on this right and the state’s obligation to prisoners. The quest for the realization of human rights by the citizenry goes in tandem with the state’s obligation to cease to violate such rights, to ensure their protection, promotion, and respect it. It avails the difference between a right and a privilege and submits that voting is not a privilege but essentially a political right. A qualitative research approach is used by re-examinig and analyzing books, articles and other relevant national and international instruments that are relevant to this work. It finally submits that The Gambia needs to undergo a reformed process in terms of state institutions, and amendment of legal instruments including the Election Act (ius constitutum) to become a law (ius constituendum) that creates equality among the people. The Constitution is both a political and legal instrument, the rights of the prisoners should be empowered by it to address the approach used through the Election Act to limit the political right of prisoners to vote.